An Automated Strabismus Classification Using Case-Based Reasoning Algorithm For Binocular Vision Management System - Muhammad Amirul Isyraf, Rohismadi (2023)
Binocular vision is a type of vision that allows an individual to perceive depth and distance using both eyes to create a single image of their environment. However, there is an illness called strabismus, where it is difficult for some people to focus on seeing things clearly at a time. There are a lot of diagnosis need to be done for doctors to diagnose whether patients suffer from strabismus or not. One of them is to perform accommodate amplitude test, which is time-consuming. Thus, with the Agile methodology, the Binocular Vision Management system is proposed which comprised of two components, a web-based component for patient, treatment, and appointment management, and a machine learning component for automating the strabismus classification by using case-based reasoning algorithm. Therefore, this will significantly hasten the process of classifying strabismus and help keep all clinical records in one place.